Impact of the information and consultation directive on industrial relations (Dublin, 2008)
"This comparative report provides a general overview of the steps taken by the 27 EU Member States and Norway to implement the 2002 Directive on informing and consulting employees in the European Community. The extent of the changes required to existing systems of information and consultation and workplace representation has varied considerably between countries. In some countries, the directive has had few, if any, implications, particularly in those with longstanding statutory works council systems; in others, it has prompted only limited amendments. However, in a number of countries, the directive has driven extensive legislative reform, for example in the UK and Ireland, where a ‘voluntarist’ industrial relations tradition predominates, and in many of the new Member States. Moreover, the transposition process has generated intense debate in some countries, in particular on the workforce-size thresholds above which undertakings or establishments are covered by information and consultation requirements, and on the nature of the employee representatives through which information and consultation takes place; the latter focus is a major issue in those countries where trade unions have traditionally been the sole or main representation channel. However, most EIRO national centres report that national measures which give effect to the directive have, as yet, had little or no impact on industrial relations practice in their countries, or that it is too early for their effects to be fully assessed."